Przydatność kondycjonowania popłuczyn wapnem w aspekcie odprowadzania wód nadosadowych do wód powierzchniowych = Advantages of lime-aided conditioning of filter backwash water in terms of discharging supernatant to ground water - Jagoszewski, Tomasz; Świderska-Bróż, Maria (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper investigates lime-aided conditioning of filter backwash water from groundwater, infiltrated and surface water treatment plants and its influence on the quality of the supernatant. A thorough analysis of contaminatian levels in the supernatant from non-conditioned and lime-conditioned backwash water has been presented.
Keywords: 2 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: zagospodarowanie zlewni" (21-22.06.2001)